2020
DOI: 10.12659/msm.922556
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Matrix Metalloproteinase Inhibitor-Eluting Stent on In-Stent Restenosis

Abstract: Background:The aim of this study was to compare changes in the extracellular matrix after implantation of a stent that elutes a matrix metalloproteinase (MMP) inhibitor (GM6001); and to determine the effects of the GM6001-eluting stent upon prevention of in-stent restenosis (ISR). Material/Methods:We included 48 Guangxi Bama mini-pigs in this study. A GM6001-eluting stent was placed in one iliac artery and a stent that did not elute GM6001 was placed in the contralateral iliac artery. The iliac arteries were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In addition, the collagen type and ratio in tissue were certain, so the change of the ratio might indicate the occurrence of some diseases, such as pulmonary fibrosis, arteriosclerosis and aneurysm, etc. The HPLC−MS method could be used to investigate the relationship between diseases and collagen change [ 38–40 ]. The degradation of implanted-collagen in vivo was usually detected by the radioactive labeling or Sirius red method, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the collagen type and ratio in tissue were certain, so the change of the ratio might indicate the occurrence of some diseases, such as pulmonary fibrosis, arteriosclerosis and aneurysm, etc. The HPLC−MS method could be used to investigate the relationship between diseases and collagen change [ 38–40 ]. The degradation of implanted-collagen in vivo was usually detected by the radioactive labeling or Sirius red method, etc.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 belongs to the matrix metalloproteinase family, which can degrade the vascular basement membrane and extracellular matrix [ 39 ], and is an important marker in the process of cell migration. The study found that overexpression of MMP-9 can promote the migration of VSMCs to the intima and reduce the content of intima matrix [ 40 ]. Therefore, the results of this experiment indicate that valsartan/sacubitril can inhibit the proliferation and migration of VSMCs induced by AngII.…”
Section: Discussionmentioning
confidence: 99%
“…The partial inhibitory mechanisms underlying the prevention of neointimal formation may be attributed to the gelatinase deficiency-caused reduction in the invasion, migration, and proliferation of VSMCs [ 36 , 37 ]. In addition, the use of a drug-eluting stent coated with a broad-spectrum MMP inhibitor (GM6001) could prevent the development of restenosis [ 38 ]. The aforementioned findings imply that suppressing MMP expression or activity can be an effective strategy for preventing neointimal formation.…”
Section: Discussionmentioning
confidence: 99%